Financial Performance Analysis of Farmer-producer Organizations in Anantapuram District of Andhra Pradesh - Ravikishore, M.; Royal, A. Prudvi; Rani, Seedari Ujwala; Chowdary, K. Raghavendra; Reddy, B. K. Kishore; Sujathamma, P.; Babu, N. Nagendra; Prasad, P. N. Siva (International Journal of Bio-resource and Stress Management, 2026)
The study was conducted during the period from September, 2020 to August, 2022 at Anantapuram district of Andhra Pradesh, India to analyse the financial viability of Farmer-Producer Organizations. This study evaluated the financial performance of five FPOs, namely Tadipatri Horticulture FPO, Sri Venkateswara Swamy FPO, Sri Ramaswamy FPO, Sri Peddamma Thalli FPO, and Narpala Rythunestam FPC in Anantapuram district of Andhra Pradesh, a drought-prone and resource-constrained region. Using audited financial statements from 2018 to 2022, key financial indicators, including current ratio, return on assets (ROA), return on equity (ROE), and debt–equity ratio, were analyzed to assess liquidity, profitability, and leverage. The findings revealed significant variations across the evaluated FPOs. Tadipatri Horticulture FPO exhibited robust profitability (ROA 0.34; ROE 0.19), while Narpala Rythunestam FPC demonstrated strong liquidity (current ratio 2.7) and efficient resource utilization (ROA 0.35). Sri Venkateswara Swamy FPO showed rapid membership and share capital growth (97%) but faced liquidity constraints (current ratio 1.04) and higher debt dependence (DER 0.89). Sri Ramaswamy and Sri Peddamma Thalli FPOs achieved moderate financial progress, though declining liquidity ratios highlighted working capital challenges. Comparative analysis suggested that the financial sustainability of FPOs is closely linked to member mobilization, equity participation, prudent debt management, and market integration. The results emphasized the need for context-specific policy support, particularly in improving access to concessional credit, strengthening value chain linkages and building managerial capacities. Overall, the study highlighted the critical role of financial health in determining the resilience and long-term sustainability of FPOs in semi-arid regions like Anantapuram district of Andhra Pradesh.